2013
DOI: 10.1007/s13277-013-1178-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional MUC4 suppress epithelial–mesenchymal transition in lung adenocarcinoma metastasis

Abstract: The mucin MUC4 is a high molecular weight membrane-bound transmembrane glycoprotein that is frequently detected in invasive and metastatic cancer. The overexpression of MUC4 is associated with increased risks for several types of cancer. However, the functional role of MUC4 is poorly understood in lung adenocarcinoma. Using antisense-MUC4-RNA transfected adenocarcinoma cells, we discovered that the loss of MUC4 expression results in epithelial-mesenchymal transition (EMT). We found morphological alterations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
0
11
1
Order By: Relevance
“…The relationship between MUC4 and EMT is also conflicting since MUC4 was shown to suppress EMT in lung adenocarcinoma in the present study [1] whereas MUC4 overexpression in ovarian cancer leads to decreased expression of epithelial markers and occurrence of mesenchymal markers via upregulation of Twist1, Twist2 and Snail transcription factors and FAK signalling pathway [12]. Collectively, these results mean that MUC4 may regulate EMT in both ways.…”
contrasting
confidence: 61%
See 1 more Smart Citation
“…The relationship between MUC4 and EMT is also conflicting since MUC4 was shown to suppress EMT in lung adenocarcinoma in the present study [1] whereas MUC4 overexpression in ovarian cancer leads to decreased expression of epithelial markers and occurrence of mesenchymal markers via upregulation of Twist1, Twist2 and Snail transcription factors and FAK signalling pathway [12]. Collectively, these results mean that MUC4 may regulate EMT in both ways.…”
contrasting
confidence: 61%
“…To the editor, Gao and collaborators have investigated the role of MUC4 in lung cancer and have concluded that loss of MUC4 results in epithelial mesenchymal transition via beta catenin nuclear translocation and that MUC4 expression is correlated with a risk of lymph node metastasis in a 20 lung adenocarcinoma patients cohort [1]. This surprising analysis is contradictory to most of the scientific knowledge and literature regarding MUC4 contribution in epithelial cancers that is very hardly discussed in their manuscript.…”
mentioning
confidence: 93%
“…38 A recent study demonstrated that MUC4 deficient lung cancer cells induced epithelial to mesenchymal transition process; decreased MUC4 expression was found in patients who had adenocarcinoma involving lymph nodes. 63 Similarly, we found that elevated expression of MUC4 was correlated with decreased proliferative capacity of lung cancer cells. 39 These contrasting observations suggest that the actual role of MUC4 in lung cancer is unclear.…”
Section: Muc4mentioning
confidence: 53%
“…In tumor cells accustomed to long-term EMT, MUC4 freely binds with molecules that normally do not appear on the non-apical surface, which contributes to a sustained state of reduced cell polarity [56]. For example, ErbB2 is normally sequestered in epithelial cells by the MUC4-ErbB2 complex, but upon the loss of cell polarity and tight junctions, ErbB3 becomes accessible for binding to ErbB2.…”
Section: Changes In Muc4 Expression In Cancer Cellsmentioning
confidence: 99%